Investigating excited electronic states using the algebraic diagrammatic construction (ADC) approach of the polarisation propagator - Wormit, Michael; Rehn, Dirk R.; Harbach, Philipp H. P.; Wenzel, Jan; Krauter, Caroline M.; Dreuw, Andreas (Molecular physics, 2014)
The development of reliable theoretical methods and the provision of efficient computer programs for the investigation of optical spectra and photochemistry of large molecules in general is one of the most important tasks of contemporary theoretical chemistry. Here, we present an overview of the current features of our implementation of the algebraic diagrammatic construction scheme of the polarisation propagator, which is a versatile and robust approach for the theoretical investigation of excited states and their properties.
Published online: 28 Oct 2013
Gesehen am 15.12.2017